2005
DOI: 10.1002/car.893
|View full text |Cite
|
Sign up to set email alerts
|

Serious case reviews: learning to use expertise

Abstract: While undertaking an analysis of 20 serious case reviews for the Welsh Assembly Government, the authors became aware of important, largely unexplored, practice issues with implications for training, service delivery and the role of the lead professional. The reviews were studied using a 'layered reading' methodology to ensure that emerging themes were grounded entirely in the reports. In looking beyond the familiar recurring themes and practice failings, findings emerged about the use of expertise in its wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Others have reported indications of conflict between agencies, especially at the outset of a case (see, for example, Hallet and Birchall, 1996). More recently, Brandon et al (2005) found that a failure to recognise and understand expertise was a significant barrier when collating information, rather than a lack of communication. This group also reported that professional insularity and lack of trust between professional groups were common barriers to rigorous assessment.…”
Section: Report On the Implementation And Evaluation Of An Interprofementioning
confidence: 98%
“…Others have reported indications of conflict between agencies, especially at the outset of a case (see, for example, Hallet and Birchall, 1996). More recently, Brandon et al (2005) found that a failure to recognise and understand expertise was a significant barrier when collating information, rather than a lack of communication. This group also reported that professional insularity and lack of trust between professional groups were common barriers to rigorous assessment.…”
Section: Report On the Implementation And Evaluation Of An Interprofementioning
confidence: 98%
“…Stanley and Manthorpe (2004), surveying different kinds of inquiry, found mixed evidence of their effectiveness in changing systems and practices. Along with others who have conducted thematic analysis of reviews (Brandon et al, 2005) they questioned whether there was sufficient energy left after report publication for translating its recommendations into action for change.…”
Section: Demonstrating Changementioning
confidence: 99%
“…In children's services safeguarding issues have been at the forefront of service provision since the Victoria Climbie inquiry (Laming, 2003) and "Every Child Matters" (2003). It has been acknowledged that the study of serious case reviews in adult services has lagged behind that in children's services (Manthorpe and Martineau, 2010), although the amount of deep learning which has taken place from children's serious case reviews is open to debate (Brandon et al, 2005;Fish et al 2008;Brandon et al 2010). Manthorpe and Martineau (2010) have noted the central role of social work managers (rather than other professions) in implementing adult protection systems.…”
Section: Philosophy and Principlesmentioning
confidence: 99%